Social Interaction Mediated by Popular Music Among University Students in the Digital Era - Huang, Shuo; Wang , Shang-wen (International Journal of Sociologies and Anthropologies Science Reviews, 2025)
Background and Aim: In the digital era, popular music has become a key medium for social interaction, identity formation, and cultural participation among university students. Digital platforms such as Spotify, TikTok, and Instagram have transformed music engagement from passive consumption into an interactive social practice. This study explores how popular music shapes students' social behaviors, examining its dual role in fostering social cohesion while potentially reinforcing exclusivity and algorithmic bias. Materials and Methods: A mixed-methods approach was employed, integrating quantitative data from structured online surveys (N=500) and qualitative insights from semi-structured interviews with a diverse sample of university students. Social Network Analysis (SNA) was used to examine patterns of music-mediated interactions, while thematic analysis of interview data provided deeper insights into students' experiences. The study also assessed the impact of algorithmic curation and sociocultural factors on students’ music engagement. Results: The findings highlight three key aspects: (1) Popular music serves as a social and identity marker, with music-sharing behaviors reinforcing peer bonds but also creating taste-based exclusivity. (2) Digital and offline music interactions are deeply interconnected, as students use online platforms to coordinate real-world social experiences such as concerts and music-themed gatherings. (3) Algorithmic personalization significantly shapes students’ musical exposure, fostering convenience while also reinforcing homophilic networks that limit cross-genre exploration. Additionally, sociocultural factors such as peer influence, generational trends, and digital literacy impact how students engage with music as a social tool. Conclusion: This study underscores the complex role of popular music in university students' digital socialization. While music strengthens peer networks and self-expression, digital infrastructures influence inclusivity and social boundaries. The findings contribute to media studies and cultural sociology by offering insights into how algorithm-driven music consumption reshapes traditional social dynamics. Future research should explore strategies to promote musical diversity and enhance the role of music as an inclusive social force in digital education and youth culture.